Functional Role of Bradyrhizobium japonicum Trehalose Biosynthesis and Metabolism Genes during Physiological Stress and Nodulation - Sugawara, Masayuki (American Society for Microbiology (ASM), 2010)
Trehalose, a disaccharide accumulated by many microorganisms, acts as a protectant during periods of physiological stress, such as salinity and desiccation. Previous studies reported that the trehalose biosynthetic genes (otsA, treS, and treY) in Bradyrhizobium japonicum were induced by salinity and desiccation stresses. Functional mutational analyses indicated that disruption of otsA decreased trehalose accumulation in cells and that an otsA treY double mutant accumulated an extremely low level of trehalose. In contrast, trehalose accumulated to a greater extent in a treS mutant, and maltose levels decreased relative to that seen with the wild-type strain. Mutant strains lacking the OtsA pathway, including the single, double, and triple ΔotsA, ΔotsA ΔtreS and ΔotsA ΔtreY, and ΔotsA ΔtreS ΔtreY mutants, were inhibited for growth on 60 mM NaCl. While mutants lacking functional OtsAB and TreYZ pathways failed to grow on complex medium containing 60 mM NaCl, there was no difference in the viability of the double mutant strain when cells were grown under conditions of desiccation stress. In contrast, mutants lacking a functional TreS pathway were less tolerant of desiccation stress than the wild-type strain. Soybean plants inoculated with mutants lacking the OtsAB and TreYZ pathways produced fewer mature nodules and a greater number of immature nodules relative to those produced by the wild-type strain. Taken together, results of these studies indicate that stress-induced trehalose biosynthesis in B. japonicum is due mainly to the OtsAB pathway and that the TreS pathway is likely involved in the degradation of trehalose to maltose. Trehalose accumulation in B. japonicum enhances survival under conditions of salinity stress and plays a role in the development of symbiotic nitrogen-fixing root nodules on soybean plants.